Risk assessment in pulmonary arterial hypertension. Issue 3 (29th March 2018) - Boucly, Athénaïs; Weatherald, Jason; Humbert, Marc; Sitbon, Olivier
We read with interest the correspondence by M.M. Hoeper and colleagues regarding risk assessment in pulmonary arterial hypertension (PAH). This follows the three manuscripts on the topic published in 2017 in the European Respiratory Journal [1, 2] and in the European Heart Journal [3]. All utilised a risk-assessment method derived from the risk-stratification table proposed by the 2015 European Society of Cardiology/European Respiratory Society Guidelines for the diagnosis and treatment of pulmonary hypertension [4, 5]. Risk stratification of pulmonary arterial hypertension based on the number of noninvasive low-risk criteria achieved at first follow-up provides an accurate identification of patients with an excellent prognosis http://ow.ly/IyNI30irqpK